Application of fracture energy for the assessment of frost degradation of high-strength concretes - Borowska, Sylwia; Kosior-Kazberuk, Marta (Budownictwo i Architektura / Civil and Architectural Engineering, 2021)
Knowledge of fracture mechanics parameters can help for a more accurate assessment of frost degradation of high-strength concrete. High strength concretes, despite the tight structure, are characterized by increased brittleness. Cracks in the concrete structure are places of accumulation of significant stresses. Additional stresses resulting from cyclic freeze/thaw stimulate the material destruction processes. The basic strength parameters of concrete do not take into account structural defects of the material and do not give a complete description of susceptibility to damage caused by, e.g., frost degradation. This study aimed to determine the relationship between frost degradation of high-strength concretes and changes in the value of their fracture energy associated with the initiation of cracking after 150, 250, 350 and 450 freeze/thaw cycles. The research was carried out using 100 × 100 × 400 mm samples, with a pre-initiated 30 mm deep notch. The I load model under a three-point bending test was used, based on the procedure recommended by RILEM. Concrete with a compressive strength of 90 MPa with steel fibres and a mixture of steel and basalt fibers was tested. The obtained results allow for the evaluation of frost degradation using fracture energy GF and critical crack tip opening displacement CTODc.